The Importance of Programs in Creating Electronic Textbooks - Sulaymanova D. B. (Zien Journals, 2024)
Electronic textbooks and them Create in the process of programs role and importance is studied . Programs electron textbooks creation , animations , interactive elements and another tools through teaching materials regularly and to the students friendly in showing help will give . Electronic textbooks and their programs through to the students mastered study experience improve data to learn facilitate and own thoughts to express opportunities emphasizes . Abstract electron of textbooks teachers and students for the most new educational and methodological from tools one as how big important have that shows
Keywords: Electronic textbooks; programs; training technologies